GADAI TANAH PERSPEKTIF EKONOMI ISLAM - Rahma Amir (MUAMALAH, 2015)
This study on land lien system, as the formulation of the problem is whether the land lien system in accordance with Islamic economic system? The purpose of this study to determine the system in relation to the ground pawn pawn in the Islamic economic system. This research was conducted using qualitative descriptive and library research (literature). In analyzing the data with data reduction, data presentation and conclusion / verification. The results showed the soil lien system in accordance with Islamic economic system in terms of the terms and the pillars, but in terms of utilization of pawning goods (land) and possession of goods pawn is not in accordance with Islamic economic system. The contribution of research to social values that provide inputs to the government, Islamic economics scholar, as well as propaganda activists to be more proactive in introducing Islamic economic system to the public, and the challenge for Islamic financial institutions to provide financial services for the community non-usury ,